Etika dan Adab Karya Tulis Ilmiah Dalam Menbangun Budaya Intelektual - Abudin Nata (Jurnal Dirosah Islamiyah, 2021)
ABSTRACT Writing scientific papers is currently growing. In addition, theses, theses, dissertations, scientific papers also include articles for scientific journals, reference books and so on. All of these works can become symbols of the progress of a nation. From these scientific works, theories, concepts, designs, innovations, novelty and so on can be produced for the progress of the nation. In order for scientific work to be beneficial and not to cause slander, fighting, provocation, and glassware that harm the people, nation and state, ethics and manners are needed in writing. The ethics and manners of writing scientific papers should not only be aimed at regulating citation methods, licensing methods, and naming of names, but also must support the progress of the people, nation and state and maintain the heterogeneous unity of the Republic of Indonesia by developing pluralist, inclusive and multicultural understanding supported by understanding wasathiyah religion. Namely the religious understanding of tawazun, takaarum, taraahum, tawathun, ta'awun, shura, i'tidal, and so on. Al-Qur'an, Hadith, the teachings of Sufism and morals in Islam are very rich to be applied in building ethics and manners for writing scientific works that are ma'rufa (good), sadida (correct), baligha (good language structure), karima (noble) , maysuura, (soft), adzima (quality) layyinan (polite), and tsaqila (firm). Keywords: ethics, intellectual cultthics, manners, writing, scientific culture